Employment law the essentials - Lewis, David; Sargeant, Malcolm; Schwab, Ben (London Kogan Page, 2023)
Employment Law is the core textbook for the CIPD Level 7 module of the same name. Easy to read, jargon-free and full of case studies and useful examples this fully updated 16th edition provides a thorough grounding in UK employment law and how it applies in practice. This definitive guide covers everything students need know to excel at their studies and begin a successful career as an HR professional. It covers the formation of the Contract of Employment, recruitment and selection, parental rights, discrimination and health and safety in the workplace. There is also essential coverage of unfair dismissal and redundancy. This new edition is completely up to date with the latest cases and legislation including updates to discrimination law and working time. There is also guidance on the legal implications of Brexit such as freedom of movement, workers' rights and the change to procedural arrangements for the final court of appeal in UK cases. Reflective activities, case studies and explore further boxes encourage critical thinking, broader engagement with the topic and a clear understanding of how employment law applies in practice, Online resources include a lecturer guide, powerpoint slides and extra case studies to support learning and enable students to apply the theory in practice"--